Non-Destructive Testing of Welds - Raj B. Baldev (New Delhi, Narosa Publishing House, 2000)
This book emphasizes the need for non-destructive testing and evaluation of welded components, with due coverage of various aspects of welding technology. It covers in detail different types of welding processes, weld defects, fitness for purpose approach, quality classes and the choice of NDT techniques including all major conventional and advanced NDT techniques. Wide coverage has been given for residual stress analysis in weldments, automation and robotics in NDT and weld related failures. Intelligent welding, fracture mechanics concepts, quality control including total quality management and codes and standards add to the unique value of the book. The whole text is structured in such a way that a lot of emphasis has been given to basic principles, applications of each technique pertaining to weld inspection and related case studies. This book will fulfill the need for professionals with overlapping interest in both welding technology and NDT. Undergraduate and postgraduate students and professionals in NDT and welding will also find it most useful